Prevalence of Cross Bite among the Orthodontic Patients at a Dental Unit of Bangladesh (Journal of National Institute of Neurosciences Bangladesh, 2019)
Background: : Cross-bite is one of the most prevalent malocclusion.Objective: This study was an attempt to find out the prevalence of crossbite in Bangladeshi population and its variation with age and gender.Methodology: This cross-sectional study was conducted in the dental unit of Rajshahi Medical College, Rajshahi, Bangladesh from January, 2017 to December, 2018. Patients who were seeking comprehensive orthodontic treatment at the OPD of Rajshahi Medical College Dental Unit, Rajshahi, Bangladesh in between 5 to 35 years of age were diagnosed for cross-bite with diagnostic model. The findings of each cases was recorded in a preformed datasheet and the descriptive analysis was performed.Result: Out of 300 cases 163(54.3%) cases had cross-bite, 90(30%) cases had anterior cross-bite and 109(36.3%) cases had posterior cross bite. Among posterior crossbite 60(20%) had unilateral and 49(16.3%) had bilateral crossbite.Conclusion: Posterior crossbite was more prevalent than anterior crossbite. Cases with Class I molar relation showed more crossbite. Crossbite was more prevalent in cases with congenitally missing teethJournal of National Institute of Neurosciences Bangladesh, 2019;5(2): 167-171